Hand Hygiene in Implementing Lifestyle Behavior Healthy On Child Age 4-5 Year - Eka Setiawati (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
The hand hygiene movement is an action that forms children's independent behavior to maintain their hands. health. The active role of parents in implementing healthy hand hygiene behavior in children is very necessary, The active role referred to is direct efforts towards children such as guiding, providing understanding, remind, And provide facility to child. Implementation behavior life Healthy hand hygiene in school is need absolute along emergence various disease Which often attack child, Which it turns out generally related to PHBS, especially related to hand washing practices (hand hygiene). The purpose of this study is to implement children's awareness of hand hygiene through the 5-day hand movement activity hygiene in Sajira District. This research method is qualitative research with data analysis using model Mills & Hubberman. Sample study as much as 12 Respondent Which taken from 5 institution school Which There is in Sajira District. Data collection techniques using observation sheets, interview notes and documentation. Results study show that role person old And school very much important in implementation behavior life healthywords